Innovative Method of the Power Analysis - Martinasek, Zdenek; Zeman, Vaclav (Společnost pro radioelektronické inženýrství, 2013)
This paper describes an innovative method of the power analysis which presents the typical example of successful attacks against trusted cryptographic devices such as RFID (Radio-Frequency IDentifications) and contact smart cards. The proposed method analyzes power consumption of the AES (Advanced Encryption Standard) algorithm with neural network, which successively classifies the first byte of the secret key. This way of the power analysis is an entirely new approach and it is designed to combine the advantages of simple and differential power analysis. In the extreme case, this feature allows to determine the whole secret key of a cryptographic module only from one measured power trace. This attribute makes the proposed method very attractive for potential attackers. Besides theoretical design of the method, we also provide the first implementation results. We assume that the method will be certainly optimized to obtain more accurate classification results in the future.
Keywords: Power analysis; Smart cards; Neural network; SPA; DPA